PENATAAN MANAJEMEN SUMBER DAYA MANUSIA APARATUR DI KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Uluputty, Irfan (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT This study focuses on aspects of human resource management of apparatus in Sumedang District. The aspects in question are (1) Job Analysis; (2) Needs Planning; and (3) Selection of Employee Candidates. The study was conducted in the Sumedang District Government. This study uses qualitative methods with descriptive approach. In connection with this study focused on local government public organizations, the general concept of staffing functions in human resource management, the researchers used the concept proposed by Dessler. The conclusions of this study include: 1) From the final results of Anjab carried out, information on the position and position map was obtained, even though in the real conditions the implementation of Anjab had not been carried out on the regional apparatus formed. 2) Planning the needs of employees and recruitment of prospective employees in Sumedang District which is carried out based on the results of Anjab with stages in: Analysis of employee needs carried out include: 1) Type of work, 2) Nature of work, 3) Analysis of workload and estimated number of civil servants in the period of time certain, 4) Principles of carrying out work, 5) Equipment available; and 6) Formulation of employee competency formation; 3) The stages of the implementation of the prospective employee selection (CPNS) in 2013 carried out covering 3 (three) stages to be followed, by the selection participants, namely: 1) Administrative Selection, 2) Basic Competency Selection, and 3) Field Competency Selection. Keywords: management arrangement, human resource management, local government